Strategies for Attention to Diverse Education in Omani Society: Perceptions of Secondary School Students - Ali Al Musawi; Wajeha Al-Ani; Azadeh Amoozegar; Khalaf Al-Abri (MDPI AG, 2022)
In a climate of increasing multiculturalism in education, classrooms have become more diverse, offering educators and institutions both opportunities and challenges. In response to changing advancements and trends in education, school administrators claim that classroom diversity can develop students' learning potential when properly harnessed and matched with inclusive pedagogy. This research reflects how diversity within the Omani education system can be enhanced by comparing the beliefs and experiences of students in diverse classrooms. This information provides a better understanding of students' learning needs based on their perception of diversity. A descriptive study was performed with a quantitative approach, whereby a sample of 283 students completed a survey. The results indicate that female students rated more highly on the teaching method scale in comparison to male students. Additional post hoc tests on simple effects confirmed that non-Arab students tend to rate their teachers comparatively more highly in terms of teaching methods, curriculum design, assessment techniques, and practical skills than Omani and Arab pupils across the different subjects. This study offers valuable insights and practical strategies for cultivating diversity and inclusion in diverse settings in Omani schools.